ULAMA TIGA SERANGKAI’S TAFSIR AL-QURANUL KARIM: Source, Method and Profiles of the Interpreters - Fadil, Muhammad Reza; Suparwany, Suparwany (Journal of Contemporary Islam and Muslim Societies, 2022)
Abstract:  Tafsir Al-Quranul Karim by Ulama Tiga Serangkai from Binjai North Sumatra has not enticed the attention of scholars of interpretation works because this indigenous text, written in 1937, has been in scarcity from circulation since halting printing. Existing research on Tafsir Al-Quranul Karim by Abdul Halim Hasan, Zainal Arifin Abbas and Abdurrahim Haitami contains misleading information concerning the date of birth of the mufassir. Likewise, the analysis of this commentary book regarding the number of verses interpreted, the sources of reference, and the method of interpretation still needs to be clarified. This study endeavours to continue the existing research by clarifying data about the originality of mufassir and completing the analysis of their commentaries by conducting interviews with the mufassir's relatives, documentation, observations at the mufassir's residences and grave sites, as well as literature study of the manuscripts of this commentary works. The study found that the mufassir in their interpretation using twenty-two books of interpretation, three mu'jams and several Islamic references written by both Muslims and orientalists and even the Bible. While the method of interpretation uses manhaj tahlili, the interpretation style is social (al-adab al-ijtimâ‘i).Keywords: Tafsir Al-Quranul Karim, Abdul Halim Hasan, Ulama Tiga Serangkai, Qur’anic exegeses, Indonesia archipelago.